An integrated framework for sustainable and efficient building maintenance operations aligning with climate change, SDGs, and emerging technology - Hauashdh, Ali; Nagapan, Sasitharan; Jailani, Junaidah; Gamil, Yaser (elsevier, 2024)
Improving the operation and maintenance of buildings can significantly reduce carbon emissions, energy consumption, and other environmental challenges while promoting sustainability. While existing literature offers various frameworks, they primarily focus on traditional building maintenance procedures and overlook the importance of integrating sustainability, climate change, environmental factors, and emerging technologies. To address this gap, this research has developed a comprehensive framework that caters to current needs, challenges, and future priorities. The integrated framework for building maintenance operations aligns with the Sustainable Development Goals (SDGs), climate change mitigation and adaptation, the adoption of emerging technology, energy conservation, as well as safety, resilience, and effectiveness. The development of the framework encompassed four phases: pre-development phases 1 and 2, development phase 3, and validation phase 4. During this process, current issues and challenges were identified, impacts were assessed, and strategies were developed. The framework serves as a roadmap to address these challenges and requirements in future building maintenance operations, making significant contributions to all three dimensions of sustainability: environmental, social, and economic. In summary, this study offers a comprehensive and in-depth analysis of the current issues, challenges, and potential improvements and benefits in building maintenance operations, providing a practical guide for industry stakeholders and making a significant contribution to the existing body of knowledge.